Paul Ricoeur : the hermeneutics of action - Ricœur, Paul; Kearney, Richard (Philosophy & social criticism (London, England), 1996)
This contains 3 major essays by Ricoeur - on Europe, fragility and responsibility, and love and justice - followed by nine key essays by internationally known experts, to provide the reader with a tour of Ricoeur's work.